Monetary policy, agent heterogeneity and inequality: Insights from a three-agent New Keynesian model - Maria Eskelinen (European Central Bank (ECB), 2021)
In this paper I develop a New Keynesian dynamic stochastic general equilibrium model which features three different types of representative agents (THRANK): the poor hand-to- mouth, the wealthy hand-to-mouth and the non-hand-to mouth households. Compared to a full-scale HANK model, this model is easier to compute while reproducing many of the same monetary policy shock transmission channels. I show that monetary policy transmission takes place through a redistribution channel, as emphasised by Auclert (2019). In particular, the effects of a monetary policy shock are amplified as resources are redistributed from high-MPC households to low-MPC households. Monetary policy therefore becomes more effective compared to models with homogeneous MPC rates. Consumption inequality is countercyclical in this setting and a high degree of leverage amplifies the redistribution channel. These findings have important implications for understanding the effects of both monetary and macroprudential policy.
Keywords: D31; E12; E21; E43; E52; 330; monetary policy; household heterogeneity; inequality; housing market